DEVELOPING HOUSEHOLD FINANCIAL LITERACY TO ADVANCE SOCIETY WELFARE IN KASEMBON, KASEMBON DISTRICT, MALANG REGENCY - Rizky Firmansyah; Tomy Rizky Izzalqurny; Adam Gumilang Rahmawan; Ach Littausil Arzaq (LPM Universitas Pasundan, 2022)
Kasembon is a developing village which has elevated potential in agricultural products. However, its society required a good financial literacy. The low knowledge of financial literacy became a demotivating factor that constructed outcome from community resource less than the maximum. Therefore, this Community Service Activity team initiated to develop the financial literacy through socialization for Kasembon Village society which assumed to improve their financial quality by transparent household financial management.